One Health risk perception among the urban vulnerable dwellers of Gujarat, India: A cross-sectional assessment - Pratiksha Ganasva; Sandul Yasobant; Krupali Patel; Deepak Saxena (​​​One Health Bulletin)
Objective: To assess One Health risk perception and local knowledge concerning threats arising from the interaction of humans, animals, and the environment at the community level with a particular emphasis on zoonotic disease transmission at Ahmedabad and Gandhinagar City, Gujarat, India, where the majority are vegetarians. Methods: A cross-sectional design with cluster sampling was employed with 387 participants participated in a quantitative survey, comprising 192 livestock handlers and 195 non-livestock handlers. Additionally, 20 in-depth interviews explored qualitative insights. Data were processed using MS Excel and analysed using Stata version 14. Results: In our study, we observed varied risk perceptions among predominantly female participants. Among livestock handlers, 23.4% acknowledged the potential for zoonotic transmission, while this awareness increased to 41.0% among non-livestock handlers. Although handwashing after animal contact and work was common among livestock handlers, only 20.3% recognized the pivotal role of hygiene in preventing zoonotic diseases. Similarly, 37.0% of livestock handlers and 47.2% of non-livestock handlers understood the risks associated with consuming raw milk and meat, which reveals a statistical difference between these two groups (P=0.000). Another significant difference was observed in the perception on animal waste disposal sites with 58.9% of livestock keepers and 80.0% of non-livestock keepers considering such sites as risky factors (P=0.000). Furthermore, vaccination awareness was high, with 85.4% of livestock handlers and 88.7% of non-livestock handlers being aware of vaccination as a preventive measure against zoonotic diseases. Interestingly, nonlivestock individuals demonstrated a higher level of awareness regarding zoonotic diseases compared to their livestock counterparts. Conclusions: This study emphasizes the urgent need for collaborative One Health interventions to address zoonotic disease risks among livestock handlers in India. By bridging knowledge gaps and promoting proactive measures, we can effectively safeguard public health and well-being in the face of emerging zoonotic threats.